Macroeconomic determinants of income inequality among different income group countries: Evidence from panel data - Basumatary, Iragdao Raja; Das, Manjit; Basumatary, Sijousa; Basumatary, Konita (Journal of Social Economics Research, 2024)
This paper investigates the macroeconomic determinants of income inequality among different income-group countries across the world by using panel data over the period from 1996 to 2019. In our research, we employ various econometric techniques to determine the model that best aligns with our purpose. Additionally, we assess the presence of autocorrelation and heteroskedasticity. Finally, we have employed FGLS and PCSE methods to estimate the impact of selected variables on income inequality and to counter the issues of autocorrelation and heteroskedasticity. Our results indicate that in low-income countries, population growth, gender equality, and globalization have a negative impact on income inequality, while HDI, civil liberty, and governance have a positive impact on income inequality. In lower-middle-income countries, economic growth, urbanization, HDI, and gender equality are inversely related to income inequality, while population growth, globalization, and governance are positively associated with income inequality. In upper-middle-income countries, urbanization, HDI, and unemployment are negatively associated with income inequality, whereas economic growth, population growth, civil liberty, and governance are positively related to it. In high-income countries, urbanization, HDI, inflation, civil liberty, globalization, and governance have a negative effect on income inequality, while economic growth, population growth, gender equality, and natural resources have a positive impact on it. The findings of the study suggest viable policy recommendations to reduce income inequality in different income-group countries.